2021
DOI: 10.1002/jez.2510
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on the jumping performance of house crickets

Abstract: Insect jumping and other explosive animal movements often make use of elastic‐recoil mechanisms to enhance performance. These mechanisms circumvent the intrinsic rate limitations on muscle shortening, allowing for greater power production as well as thermal robustness of the associated movements. Here we examine the performance and temperature effects on jumping in the house cricket, Acheta domesticus, using high‐speed imaging and inverse dynamics analysis. We find that adult house crickets jumped with greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Thermal robustness through elastic recoil is observed in chameleon and salamander tongue projection, and ballistic mouth opening in frogs and toads, but less so in frog or house cricket jumping ( Hirano and Rome, 1984 ; Anderson and Deban, 2010 ; Deban and Richardson, 2011 ; Deban and Lappin, 2011 ; Scales et al, 2017 ; Olberding and Deban, 2021 ; Deban and Anderson, 2021 ). Deban and Anderson (2021) showed that jumping performance in house crickets was relatively more temperature sensitive than jumping in fleas and other insects despite use of elastic recoil mechanisms. The authors suggest that this could be due to additional muscle contributions during the takeoff phase, or dealing with high loads, which are known to result in temperature-dependent work outputs ( Olberding and Deban, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal robustness through elastic recoil is observed in chameleon and salamander tongue projection, and ballistic mouth opening in frogs and toads, but less so in frog or house cricket jumping ( Hirano and Rome, 1984 ; Anderson and Deban, 2010 ; Deban and Richardson, 2011 ; Deban and Lappin, 2011 ; Scales et al, 2017 ; Olberding and Deban, 2021 ; Deban and Anderson, 2021 ). Deban and Anderson (2021) showed that jumping performance in house crickets was relatively more temperature sensitive than jumping in fleas and other insects despite use of elastic recoil mechanisms. The authors suggest that this could be due to additional muscle contributions during the takeoff phase, or dealing with high loads, which are known to result in temperature-dependent work outputs ( Olberding and Deban, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, peak velocity, acceleration, and power of elastically actuated tongue projection in chameleons shows Q 10 values that range from 1.1-1.3 across 15-25°C indicating Journal of Experimental Biology • Accepted manuscript that tongue projection is relatively insensitive to the change in temperature (Anderson and Deban 2010). Thermal robustness through elastic recoil has also been observed in salamander tongue projection (Deban and Richardson 2011;Scales et al 2017;Deban et al 2021) and anuran tongue projection and ballistic mouth opening (Deban and Lappin 2011;Sandusky and Deban 2012) suggesting that elastic recoil mechanisms underlie thermally robust behaviors in some ectothermic organisms.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A. domesticus is an excellent and often used model organism due to its many advantages, such as its small size, ease of rearing, short life cycle, nutrient richness, lack of diapause, high tolerance and ease of handling ( Clifford et al, 1977 ; Crocker and Hunter, 2018 ). These advantages make this species ideal for research on the development and utilization of edible and forage insects ( Patton, 1978 ; Grossmann et al, 2021 ; Khatun et al, 2021 ), immune regulation ( Piñera et al, 2013 ), adult neurogenesis ( Cayre et al, 2007 ), and other topics ( Nelson and Nolen, 1997 ; Fuciarelli and Rollo, 2020 ; Deban and Anderson, 2021 ; Li and Rollo, 2021 ). Moreover, after A. domesticus eclosion, their flight muscles degraded, and some but not all individuals shed their hind wings, resulting in wing dimorphism.…”
Section: Introductionmentioning
confidence: 99%
“…Critically, such movements are thermally robust: Elastic-based mechanisms operate equally well (or better) across a broader range of temperatures without substantial performance decrement ( Deban and Lappin 2011 ; Quenta Herrera et al. 2018 ; Deban and Anderson 2021 ).…”
Section: Introductionmentioning
confidence: 99%